PENDIDIKAN KESEHATAN TENTANG PERAWATAN SELAMA KEHAMILAN DAN PERSIAPAN PERSALINAN SELAMA MASA PANDEMI COVID-19 - Daevi Khairunisa; Ismaulidia Nurvembrianti; Mita Sarinida (Politeknik 'Aisyiyah Pontianak, 2022)
The pandemic of COVID-19 might affect the health of women during pregnancy. There is still limited information regarding the impact of COVID-19 on pregnant women. Antenatal and prenatal care education is needed for pregnant women, especially during this pandemic of COVID-19. Aim: To increase the level of knowledge about antenatal and prenatal care among pregnant women during the pandemic of COVID-19. Method: The activity was delivered through lectures, and pre-and post-test was taken before and after the lecture, respectively. The participant involved was 12 pregnant women. This Pengabdian Kepada Masyarakat (Community Service Program) was conducted in Sungai Bemban Village, Kubu District, Kubu Raya Regency. Result: The descriptive analysis shows that there is an increase in the level of knowledge in pre-and post-test, from poor (50%) to good (67%). Conclusion: The activity went well amid the pandemic of COVID-19. Health education for pregnant women during the pandemic of COVID-19 may be beneficial for the preparation of a healthy and safe delivery. Pregnant women can still consult and undergo antenatal care safely by observing the health protocol.